Strategic Integration of Surgical Techniques for Knee Preservation: A Case Report - Jaramillo-Quiceno A; Sarmiento-Riveros PA; Arias-Perez RD; Mejia-Bustamante OA; Guzman-Benedek RD (Malaysian Orthopaedic Journal)
Different surgical techniques are used to preserve knee articular cartilage deterioration; however, combining these techniques can be challenging. This case study describes a 35-year-old man with bilateral genu varum malalignment and left knee pain, diagnosed with a grade IV chondral lesion in the lateral femur, a complex lateral meniscus lesion, and a radial tear in the medial meniscus. The patient underwent a valgus-producing tibial osteotomy, lateral osteochondral allograft transplantation, and lateral meniscal allograft transplantation using a 3D model of the proximal tibia. Seventeen months post-operatively, he experienced torsional trauma, leading to a tear of the transplanted meniscus posterior root and an anterior cruciate ligament injury. Subsequent surgical exploration revealed evidence of chondroprotective changes, including femoral osteochondral allograft healing and biomechanical integration of the transplanted meniscus, as indicated by the lateral meniscus root tear development. This case highlights the potential of combining these surgical procedures to achieve biomechanical integration of the transplanted meniscus, contributing to cumulative chondroprotective effects.